2021
DOI: 10.1002/jnm.2877
|View full text |Cite
|
Sign up to set email alerts
|

Heterodielectric oxide‐engineered single‐lateral pocket‐based gated source TFET

Abstract: In this work, we propose and investigate a new pocket‐based Si0.55Ge0.45/Si gate normal tunnel FET design employing a gate over source with a single lateral pocket (GSLP) with and without a heterogeneous dielectric (HD) gate oxide. Miller capacitance is significantly reduced with the GSLP design, which is further improved by the HD gate oxide leading to full overshoot/undershoot suppression capability in transient response. Further, a steep switching with more than one order improvement in ON current is achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The tunneling field-effect transistor (TFET) is a promising device to replace the conventional MOSFET as a transistor as well as a biosensor. It is devoid of the abovementioned issues present in the conventional MOSFET as its operation relies on quantum mechanical tunneling. , TFETs, on the other hand, display ambipolar conduction, which is the flow of drain current for both polarities of the gate voltage. It relies on the band-to-band tunneling (BTBT) of carriers at the interface between the drain/channel and also on dielectric constant.…”
Section: Introductionmentioning
confidence: 99%
“…The tunneling field-effect transistor (TFET) is a promising device to replace the conventional MOSFET as a transistor as well as a biosensor. It is devoid of the abovementioned issues present in the conventional MOSFET as its operation relies on quantum mechanical tunneling. , TFETs, on the other hand, display ambipolar conduction, which is the flow of drain current for both polarities of the gate voltage. It relies on the band-to-band tunneling (BTBT) of carriers at the interface between the drain/channel and also on dielectric constant.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been observed that TFETs suffer from two major drawbacks: (i) the low ON current and (ii) its ambipolar behaviour. Different approaches have been adopted to improve ON current, viz., hetero gate dielectric [5,6], heterojunction TFET [7,8], multigate technology [9,10], gate all around (GAA) structures [11], and pocket doping [12,13]. Gate work function engineering, high-K stacked gate oxide layers [14], and other techniques have also been followed for enhancing the ON current while keeping the OFF current under control.…”
Section: Introductionmentioning
confidence: 99%
“…A hetero-dielectric gate (HDG) TFET has been proposed by researchers to increase the on-current and suppress the ambipolar current in the device. [30][31][32][33][34] In this proposed structure, high-κ oxide is placed near the source to induce a local minima of conduction band edge of the tunneling junction and low-κ oxide is placed near drain to suppress the ambipolar current. The electrical characteristics of these HDG TFET devices are mostly predicted with the help of TCAD simulator.…”
Section: Introductionmentioning
confidence: 99%